Learners' flow experience during peer revision in a virtual writing course during the global pandemic. (April 2022) - Payant, Caroline; Zuniga, Michael
Abstract: The global Covid-19 pandemic that hit educational contexts worldwide transformed our regular educational practices and some tasks such as peer revision, a staple in many additional language (AL) writing courses (Hyland & Hyland, 2019), were put aside. As teachers have become more familiar with many new technologies since the start of the pandemic, there is a need to implement peer revision tasks in virtual spaces and to understand learners' experiences in this process. The aims of the present study were to examine AL learners' subjective experience through flow theory as they engage in peer revision tasks with two components: an individual peer feedback component with a follow-up shared feedback component. Flow, a positive experiential state characterized by focus and involvement in challenging yet doable tasks, has been associated with enhanced self-confidence and task performance (Csikszentmihalyi, 2008). Participants of French as an AL (n = 18) engaged in two peer revision tasks (PR) which included both an individual (I-PR) and a follow-up sharing component (S-PR). Flow perception questionnaires were completed immediately following each task. Findings provide empirical evidence that despite being physically isolated and having limited experience with online technologies, learners experienced flow, especially during the S-PR component.